THE PLACE OF UNIVERSAL HUMAN VALUES IN THE FAMILY (British Journal of Global Ecology and Sustainable Development, 2024)
It is no exaggeration to say that the topic of this article is one of the most pressing issues of renewal in the era of globalization. Because in the period when every democratic and civil society is being built, universal human values, morals of parents, affection for children, faith, belief, and universal values of traditions are highlighted in the family.